Answer:
a perfect square because 17 x 17 = 289
It's not a perfect cube
Step-by-step explanation:
Answer:
6x−7
Step-by-step explanation:
2x−7+4x
=2x+−7+4x
Combine Like Terms:
=2x+−7+4x
=(2x+4x)+(−7)
=6x+−7
Answer: x^4
Step-by-step explanation:
1. Rewrite the expression in fraction form:
(3√x²)^6 = x^(2/3)^6
2 is the exponent, so when written in fraction form, it is the numerator. 3 is the index or root, so in fraction form it is the denominator.
2. Solve:
x^(2/3)^6 = x^(12/3) = x^4
Because the exponent 2/3 is raised to the power of 6, you can use the power rule, which basically just means that whenever an exponent is raised to an exponent, multiply them. So, 2/3 * 6 equals 12/3, and 12/3 equals 4, making your answer x^4.
Answer:
y=2x-8
Step-by-step explanation:
y-y1=m(x-x1)
y-4=2(x-6)
y=2x-12+4
y=2x-8